Choking, allergic reactions, and pickiness: A qualitative study of maternal perceived threats and risk avoidance strategies during complementary feeding. (1st April 2022) - Graf, Michelle Dorsey; Lutenbacher, Melanie; Wasser, Heather; Dietrich, Mary S.; Karp, Sharon M.
Abstract: An infant's early eating experiences influence later growth and health. However, motivators for mothers' complementary feeding decisions for their infants, such as the process of introducing solid foods, remains unclear. This qualitative study identified maternal perceived threats surrounding complementary feeding and strategies mothers use to mitigate perceived threats of adverse feeding-related health outcomes for their infants. Twenty-seven mothers participated in private, semi-structured interviews. Inductive and deductive qualitative content analysis revealed three primary themes of maternal perceived threats: a) choking, b) allergic reaction, and c) pickiness. Within each primary theme were sub-themes that further delineated the perceived threats and outlined specific and focused complementary feeding practices (CFPs) mothers used for each type of perceived threat. Findings suggest mothers have difficulty with estimating the likelihood and severity of risks and rely on elevated threat perception to guide their feeding decisions. CFPs used to prevent perceived threats were disproportionate to risks, and, at times, actually introduced additional, alternative risks.